Typology of the British Novel of the end of the XX – early XXI Centuries: Scientific Approach of the Post-postmodern Transformations - Дроздовський, Дмитро Ігорович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In the paper, the transformational dynamics of contemporary British novel has been spotlighted taking into account such key subgenres as historiographic metafiction, neo-Victorian novel, novel-biography, cross-cultural (postcolonial) novel, “novel of the English idea”. The epistemological problems explicated the British post-postmodern novel (1990-2010-s.) – undifferentiated perception of true and false reality, using the scientific approaches for the explication of the human nature – have been analyzed in the paper.